Nitrogen-sulfur modified graphene coated positive electrode material and preparation method and application thereof
By coating the modified cathode material with nitrogen and sulfur double-doped graphene, the problem of graphene prone agglomeration and low activity in the prior art is solved, the conductivity and ion transport efficiency are improved, the process is simplified and the production efficiency is improved.
Patent Information
- Application Number
- CN202411906230.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
AI Technical Summary
The existing graphene modified cathode materials have graphene easily agglomerated, low activity, low transmission efficiency of electrons and ions, and the preparation process is cumbersome, the cycle is long, the production efficiency is low, and the coating effect is poor.
The coating and modification of the positive electrode material was carried out by using nitrogen and sulfur double-doped graphene. By mixing thiourea with graphene oxide, forming a modified liquid and the positive electrode material and spray-drying treatment, a positive electrode material uniformly coated with nitrogen and sulfur modified graphene was prepared.
The conductive and ion transport efficiency of graphene are improved, the structural stability and thermal stability of the material are enhanced, the electrochemical performance is improved, and the process is simplified by spray drying and production efficiency is improved.
Smart Images

Figure CN119695122A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials and relates to a nitrogen-sulfur modified graphene coated positive electrode material and a preparation method and application thereof. Background Art
[0002] With the development of new energy technologies, the demand for high-performance battery materials is growing. Positive electrode materials are widely used in lithium-ion batteries due to their high energy density and good cycle stability. However, positive electrode materials are prone to structural damage and interface instability during the charge and discharge process, resulting in battery performance degradation. Graphene is considered to be an ideal coating material to improve the performance of positive electrode materials due to its excellent conductivity and mechanical strength.
[0003] CN118263413A discloses a graphene-modified lithium-ion battery positive electrode material and a preparation method thereof, wherein the graphene-modified lithium-ion battery positive electrode material is obtained by mixing graphene and a lithium-ion positive electrode material, performing primary dispersion, drying, hot pressing calcination, crushing and secondary dispersion.
[0004] CN115784326A discloses a hydroxide positive electrode precursor and its preparation method and application. The preparation method comprises the following steps: (1) adding a nickel-cobalt-manganese metal salt solution, a dopant solution, a precipitant solution and a complexing agent solution to a base liquid in parallel to perform a coprecipitation reaction to obtain a precursor to be treated; (2) coating the precursor to be treated in step (1), graphene and an organic solvent to obtain a graphene-coated hydroxide positive electrode precursor.
[0005] In the graphene-modified positive electrode material described in the above scheme, graphene is easy to agglomerate, has low activity and low transmission efficiency of electrons and ions, and the preparation process of the positive electrode material is complicated, the process cycle is lengthy, and the production efficiency is low. In addition, it is difficult to fully mix the coating material and the positive electrode material during the coating process, and the coating effect is not good. Summary of the invention
[0006] The purpose of the present invention is to provide a nitrogen-sulfur modified graphene coated positive electrode material and a preparation method and application thereof. The present invention utilizes nitrogen-sulfur dual-doped graphene to coat and modify the positive electrode material, and after a one-step spray drying process, a positive electrode material uniformly coated with nitrogen-sulfur doped graphene is prepared, which has excellent electrochemical charge and discharge capabilities and cycle performance.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a nitrogen-sulfur modified graphene coated positive electrode material, the preparation method comprising the following steps:
[0009] (1) mixing thiourea with a graphene oxide dispersion to obtain a modified solution;
[0010] (2) The modified liquid is mixed with the positive electrode material, and the mixture is spray-dried to obtain the nitrogen-sulfur modified graphene coated positive electrode material.
[0011] In the preparation process of the nitrogen-sulfur modified graphene coated positive electrode material of the present invention, thiourea not only acts as a reducing agent to reduce graphene oxide to graphene, but also can participate in the formation of sulfide as a sulfide precursor, forming CSC bonds, and enhancing the stability and conductivity of the material. The present invention uses thiourea to modify graphene oxide with nitrogen and sulfur dual doping, thereby increasing the number of active sites on the graphene surface, further improving the conductivity and ion transmission efficiency of the coated material, and having better electrochemical performance, structural stability and thermal stability than ordinary graphene coating. Coating by spray drying can further improve the stability of the positive electrode material and the transmission capacity of ions and electrons.
[0012] Preferably, the solvent of the graphene oxide dispersion in step (1) includes any one of ethanol, N,N-dimethylformamide, N-methyl-2-pyrrolidone, ethylene glycol, acetone or dimethyl sulfoxide, or a combination of at least two thereof.
[0013] Preferably, the mass concentration of the graphene oxide dispersion in step (1) is 0.1 g / L to 0.2 g / L, for example, 0.1 g / L, 0.12 g / L, 0.15 g / L, 0.18 g / L or 0.2 g / L, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] Preferably, the mass ratio of graphene oxide to thiourea in the graphene oxide dispersion in step (1) is 1:(20-40), for example: 1:20, 1:25, 1:30, 1:35 or 1:40, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] Preferably, the positive electrode material in step (2) includes any one of nickel-cobalt-manganese ternary positive electrode material, lithium cobalt oxide positive electrode material, lithium-rich manganese-based positive electrode material, lithium iron phosphate positive electrode material or lithium iron manganese phosphate positive electrode material, or a combination of at least two thereof.
[0016] Preferably, the mass ratio of the total mass of thiourea and graphene oxide in the modified solution of step (2) to the mass ratio of the positive electrode material is (0.5-2):100, for example: 0.5:100, 0.8:100, 1:100, 1.5:100 or 2:100, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] Preferably, stirring is performed during the mixing process in step (2).
[0018] Preferably, the stirring time is 5 min to 15 min, for example, 5 min, 8 min, 10 min, 12 min or 15 min, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0019] Preferably, the inlet air temperature of the spray drying treatment in step (2) is 200°C to 250°C, for example, 200°C, 210°C, 220°C, 230°C, 240°C or 250°C, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] Preferably, the outlet air temperature of the spray drying treatment in step (2) is 80°C to 120°C, for example, 80°C, 90°C, 100°C, 110°C or 120°C, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] In a second aspect, the present invention provides a nitrogen-sulfur modified graphene coated positive electrode material, wherein the nitrogen-sulfur modified graphene coated positive electrode material is prepared by the preparation method described in the first aspect.
[0022] Preferably, the nitrogen-sulfur modified graphene coated positive electrode material comprises a positive electrode material core and a nitrogen-sulfur modified graphene coating layer disposed on the surface of the positive electrode material core.
[0023] Preferably, the thickness of the nitrogen-sulfur modified graphene coating layer is 2 nm to 3 nm, for example, 2 nm, 2.2 nm, 2.5 nm, 2.8 nm or 3 nm.
[0024] Preferably, based on the mass of the nitrogen-sulfur modified graphene coated positive electrode material being 100%, the mass fraction of the nitrogen-sulfur modified graphene coating layer is 1.5% to 2%, for example: 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%, etc.
[0025] In a third aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the nitrogen-sulfur modified graphene-coated positive electrode material as described in the second aspect.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The present invention uses thiourea to perform nitrogen-sulfur dual doping modification on graphene. The nitrogen-sulfur dual doped graphene is not easy to agglomerate and has high electrochemical activity. The nitrogen-sulfur dual doped graphene contains unsaturated conjugated carbon atoms that significantly increase the conductivity, and the surface active sites are increased, which is conducive to better promoting the formation of a conductive network and improving the transmission efficiency of electrons and ions. Afterwards, the coating is carried out by spray drying, which can not only achieve uniform coating, but also greatly improve production efficiency, and is suitable for large-scale production.
[0028] (2) The 0.1C discharge specific capacity of the battery made of the nitrogen-sulfur modified graphene coated positive electrode material (for NCM811) of the present invention can reach more than 199.62mAh / g, the 0.2C discharge specific capacity can reach more than 192.9mAh / g, the 0.5C discharge specific capacity can reach more than 187.59mAh / g, the 1C discharge specific capacity can reach more than 181.5mAh / g, and the capacity retention rate after 100 cycles at 1C can reach more than 88.8%. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the SEM image of the nitrogen-sulfur modified graphene coated positive electrode material obtained in Example 1. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0031] Example 1
[0032] This embodiment provides a nitrogen-sulfur modified graphene coated positive electrode material, and the nitrogen-sulfur modified graphene coated positive electrode material is prepared by the following method:
[0033] (1) forming a uniform graphene oxide dispersion in ethanol with a concentration of 0.15 g / L, and mixing the graphene oxide dispersion with thiourea at a mass ratio of 1:30 to obtain a modified solution;
[0034] (2) The modified liquid and the NCM811 positive electrode material are stirred for 10 minutes in a mass ratio of the total mass of graphene oxide and thiourea to the NCM811 positive electrode material of 1:100 until they are fully mixed, and the obtained mixed liquid is spray-dried at an inlet air temperature of 220°C and an outlet air temperature of 100°C to obtain the nitrogen-sulfur modified graphene coated positive electrode material.
[0035] In the nitrogen-sulfur modified graphene coated positive electrode material, the thickness of the nitrogen-sulfur modified graphene coating layer is 2nm, and the mass fraction of the nitrogen-sulfur modified graphene coating layer is 1.6%. The SEM image of the nitrogen-sulfur modified graphene coated positive electrode material is as follows Figure 1 shown.
[0036] Example 2
[0037] This embodiment provides a nitrogen-sulfur modified graphene coated positive electrode material, and the nitrogen-sulfur modified graphene coated positive electrode material is prepared by the following method:
[0038] (1) forming a uniform graphene oxide dispersion in ethanol with a concentration of 0.18 g / L, and mixing the graphene oxide dispersion with thiourea at a mass ratio of 1:20 to obtain a modified solution;
[0039] (2) The modified liquid and the NCM811 positive electrode material are stirred for 15 minutes in a mass ratio of 2:100 of the total mass of graphene oxide and thiourea to the NCM811 positive electrode material until they are fully mixed, and the obtained mixed liquid is spray-dried at an inlet air temperature of 200° C. and an outlet air temperature of 80° C. to obtain the nitrogen-sulfur modified graphene coated positive electrode material.
[0040] In the nitrogen-sulfur modified graphene coated positive electrode material, the thickness of the nitrogen-sulfur modified graphene coating layer is 3 nm, and the mass fraction of the nitrogen-sulfur modified graphene coating layer is 1.7%.
[0041] Example 3
[0042] This embodiment provides a nitrogen-sulfur modified graphene coated positive electrode material, and the nitrogen-sulfur modified graphene coated positive electrode material is prepared by the following method:
[0043] (1) forming a uniform graphene oxide dispersion in ethanol with a concentration of 0.12 g / L, and mixing the graphene oxide dispersion with thiourea at a mass ratio of 1:40 to obtain a modified solution;
[0044] (2) The modified liquid and the NCM811 positive electrode material are stirred for 10 minutes according to the mass ratio of the total mass of graphene oxide and thiourea to the NCM811 positive electrode material of 0.5:100 until they are fully mixed, and the obtained mixed liquid is spray-dried at an inlet air temperature of 250°C and an outlet air temperature of 120°C to obtain the nitrogen-sulfur modified graphene coated positive electrode material.
[0045] In the nitrogen-sulfur modified graphene coated positive electrode material, the thickness of the nitrogen-sulfur modified graphene coating layer is 2 nm, and the mass fraction of the nitrogen-sulfur modified graphene coating layer is 1.43%.
[0046] Example 4
[0047] The only difference between this embodiment and embodiment 1 is that the mass ratio of graphene oxide to thiourea is 1:10, and other conditions and parameters are exactly the same as those in embodiment 1.
[0048] Example 5
[0049] The only difference between this embodiment and embodiment 1 is that the mass ratio of graphene oxide to thiourea is 1:50, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0050] Example 6
[0051] The only difference between this embodiment and embodiment 1 is that the mass ratio of the total mass of thiourea and graphene oxide to the mass of the positive electrode material is 0.1:100, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0052] Example 7
[0053] The only difference between this embodiment and embodiment 1 is that the mass ratio of the total mass of thiourea and graphene oxide to the mass of the positive electrode material is 3:100, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0054] Example 8
[0055] The only difference between this embodiment and embodiment 1 is that the air inlet temperature of the spray drying process is 150° C., and the other conditions and parameters are exactly the same as those of embodiment 1.
[0056] Example 9
[0057] The only difference between this embodiment and embodiment 1 is that the air inlet temperature of the spray drying process is 300° C., and the other conditions and parameters are exactly the same as those of embodiment 1.
[0058] Comparative Example 1
[0059] The only difference between this comparative example and Example 1 is that thiourea is not added, and other conditions and parameters are exactly the same as those in Example 1.
[0060] Comparative Example 2
[0061] The only difference between this comparative example and Example 1 is that thiourea is replaced with an equal amount of urea for nitrogen doping, and the other conditions and parameters are exactly the same as those in Example 1.
[0062] Comparative Example 3
[0063] The only difference between this comparative example and Example 1 is that thiourea is replaced with an equal amount of sulfur for sulfur doping, and the other conditions and parameters are exactly the same as those in Example 1.
[0064] Comparative Example 4
[0065] The only difference between this comparative example and Example 1 is that conventional wet coating and subsequent drying are used, and other conditions and parameters are exactly the same as those in Example 1.
[0066] Performance Test:
[0067] The positive electrode material, conductive carbon black and PVDF prepared in the embodiment and the comparative example were weighed and mixed according to a mass ratio of 90:5:5, and a positive electrode slurry was prepared after adding a solvent NMP. The slurry was evenly coated on an aluminum foil material and baked at 105°C for 1 hour. The baked pole piece was cut and placed in a tablet press for compaction at 25Mpa, and small discs were cut out and assembled under a nitrogen atmosphere. The small discs were placed in the positive side of the buckle battery housing with the fluorine-coated side facing the positive electrode, and 50 μL of 1 mol / L electrolyte (EC, EMC and DMC with a volume ratio of 1:1:1) was dripped in, a diaphragm was placed in, and 50 μL of electrolyte was dripped in, a pure lithium sheet, a gasket, and a spring were placed in the buckle battery negative electrode housing, and the battery was packaged into a CR2032 button battery. The rate performance and cycle performance were tested. The test results are shown in Table 1:
[0068] Table 1
[0069]
[0070]
[0071] As can be seen from Table 1, from Examples 1-9, the 0.1C discharge specific capacity of the battery made of the nitrogen-sulfur modified graphene-coated positive electrode material of the present invention can reach more than 199.62 mAh / g, the 0.2C discharge specific capacity can reach more than 192.9 mAh / g, the 0.5C discharge specific capacity can reach more than 187.59 mAh / g, the 1C discharge specific capacity can reach more than 181.5 mAh / g, and the capacity retention rate after 100 cycles at 1C can reach more than 88.8%.
[0072] By comparing Example 1 with Examples 4-5, it can be seen that in the preparation process of the nitrogen-sulfur modified graphene coated positive electrode material of the present invention, the ratio of graphene oxide to thiourea will affect its performance. The mass ratio of graphene oxide to thiourea is controlled at 1: (20-40), and the performance of the nitrogen-sulfur modified graphene coated positive electrode material is better. If the proportion of thiourea is too high, too many defects will be introduced, affecting the stability and cycle performance of the material. If the proportion of thiourea is too low, the electronic structure of graphene is not significantly changed, and no significant improvement effect is achieved.
[0073] By comparing Example 1 with Examples 6-7, it can be seen that in the preparation process of the nitrogen-sulfur modified graphene coated positive electrode material of the present invention, the ratio of the total mass of thiourea and graphene oxide to the positive electrode material will affect its performance. The total mass of thiourea and graphene oxide is controlled to have a mass ratio of (0.05-2):100, and the performance of the nitrogen-sulfur modified graphene coated positive electrode material is better. If the addition amount of thiourea and graphene oxide is too high, the coating layer will be thicker, which will affect the deintercalation of lithium ions. If the addition amount of thiourea and graphene oxide is too low, the coating effect will not be achieved, and an effective three-dimensional electronic interconnection channel cannot be formed.
[0074] By comparing Example 1 with Examples 8-9, it can be seen that in the preparation process of the nitrogen-sulfur modified graphene coated positive electrode material of the present invention, the inlet air temperature of the spray drying treatment will affect its performance. The inlet air temperature of the spray drying treatment is controlled at 200°C to 250°C, and the performance of the nitrogen-sulfur modified graphene coated positive electrode material is better. If the inlet air temperature of the spray drying treatment is too high, the carbon material will undergo a coking reaction, changing the structure of the material. If the inlet air temperature of the spray drying treatment is too low, the moisture content of the material will be too high, and the material particles will easily agglomerate, affecting the transmission of lithium ions and electrons.
[0075] By comparing Example 1 and Comparative Examples 1-3, it can be seen that the present invention uses thiourea to perform nitrogen-sulfur dual-doping modification on graphene, and the nitrogen-sulfur dual-doped graphene is not easy to agglomerate and has high electrochemical activity. The nitrogen-sulfur dual-doped graphene contains unsaturated conjugated carbon atoms that significantly increase the conductivity, and the surface active sites are increased, which is conducive to better promoting the formation of a conductive network and improving the transmission efficiency of electrons and ions.
[0076] From the comparison between Example 1 and Comparative Example 4, it can be seen that the coating by spray drying in the present invention cannot improve the uniformity of the coating layer on the surface of the positive electrode material, thereby improving the performance of the material.
[0077] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a nitrogen-sulfur modified graphene coated positive electrode material, characterized in that: The preparation method comprises the following steps: (1) mixing thiourea with a graphene oxide dispersion to obtain a modified solution; (2) The modified liquid is mixed with the positive electrode material, and the mixture is spray-dried to obtain the nitrogen-sulfur modified graphene coated positive electrode material.
2. The preparation method according to claim 1, characterized in that The solvent of the graphene oxide dispersion in step (1) includes any one of ethanol, N,N-dimethylformamide, N-methyl-2-pyrrolidone, ethylene glycol, acetone or dimethyl sulfoxide, or a combination of at least two thereof.
3. The preparation method according to claim 1 or 2, characterized in that: The mass concentration of the graphene oxide dispersion in step (1) is 0.1 g / L to 0.2 g / L.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The mass ratio of graphene oxide to thiourea in the graphene oxide dispersion of step (1) is 1:(20-40).
5. The preparation method according to any one of claims 1 to 4, characterized in that: The positive electrode material in step (2) includes any one of nickel-cobalt-manganese ternary positive electrode materials, lithium cobalt oxide positive electrode materials, lithium-rich manganese-based positive electrode materials, lithium iron phosphate positive electrode materials or lithium iron manganese phosphate positive electrode materials, or a combination of at least two thereof.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The mass ratio of the total mass of thiourea and graphene oxide in the modified solution of step (2) to the mass ratio of the positive electrode material is (0.5-2):
100.
7. The preparation method according to any one of claims 1 to 6, characterized in that: Stirring during the mixing process of step (2); Preferably, the stirring time is 5 min to 15 min.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The inlet air temperature of the spray drying process in step (2) is 200°C to 250°C; Preferably, the outlet air temperature of the spray drying process in step (2) is 80°C to 120°C.
9. A nitrogen-sulfur modified graphene coated positive electrode material, characterized in that: The nitrogen-sulfur modified graphene coated positive electrode material is prepared by the preparation method according to any one of claims 1 to 8; The nitrogen-sulfur modified graphene coated positive electrode material comprises a positive electrode material core and a nitrogen-sulfur modified graphene coating layer arranged on the surface of the positive electrode material core; The thickness of the nitrogen-sulfur modified graphene coating layer is 2nm to 3nm; Taking the mass of the nitrogen-sulfur modified graphene coated positive electrode material as 100%, the mass fraction of the nitrogen-sulfur modified graphene coating layer is 1.5% to 2%.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the nitrogen-sulfur modified graphene-coated positive electrode material as claimed in claim 9.